Wie immer herzliche Grüße - Brandt, Nancy; Simon, Helen (Germany : HFF Munchen, 2009)
The filmmakers set out on a journey to explore the effects of the separation of Germany and find out what has become of east and west. Karl-Heinz lived in the GDR. He used to write letters to his friend Gerhard in West Germany. Over 30 years of correspondence tell the story of the separation of the country. These letters accompany us through the entire film.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films